The Competitiveness of Indonesian Natural Rubber in World Trade on the Agreed Export Tonnage Scheme Policy - Aripranata, Aripranata; Na Ayutthaya, Supat Isarangkool; Choenkwan, Sukanlaya (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 18 No 2 (2024): Vol 18 No 2 (2024)DO - 10.24843/SOCA.2024.v18.i02.p01, 2024)
The agricultural sector, particularly natural rubber commodities, is experiencing rapid development, especially in Indonesia, the biggest producing nation for rubber worldwide. A product is considered competitive if it can compete effectively in the market. High competitiveness in a product is reflected in its good price and quality. However, if a product cannot compete, it will lead to new problems. Therefore, various analyses, such as the competitiveness analysis of Indonesian natural rubber, are necessary. This research aims to analyze the competitiveness of Indonesian natural rubber and explain the factors influencing this competitiveness. Annual data from 2000 to 2002 was collected from the Food and Agriculture Organization of the United Nations, the World Bank, the World Trade Organization, the Ministry of Agriculture of the Republic of Indonesia, and the Ministry of Trade of the Republic of Indonesia. A quantitative approach using the Ordinary Least Squares (OLS) method is employed. The research is conducted in Indonesia due to its status as one of the countries with the highest natural rubber production value globally. The analysis tools used include Microsoft Excel and SPSS 28.0.1.0. The results of the competitiveness analysis indicate that Indonesian natural rubber farming has a competitive advantage in world trade. Of the four factors affecting competitiveness, only Indonesia's natural rubber production shows significance, while the exchange rate, export value, and policies do not have a significant impact